A study on the factors to improve the sale performance of CIMB Wealth Advisory service among clients or investors / Suzana Gapor - Gapor, Suzana (2012)
In this study, the researcher conducts a study to improve sales performance of CIMB Wealth Advisory service among the client or investor. The study helps the researcher to determine the potential client or investor in Shariah-compliant funds in CIMB Wealth Advisory. Other than that the study also helps the researcher to identify the factors to improve sales performance of CIMB Wealth Advisory service among clients or investor. The information that gathered from this research helps the researcher to make a recommendation for CIMB Wealth advisory. Thus, the study helps CIMB Wealth Advisory to improve its performance and staffs. The study also helps CIMB Wealth Advisory to improve sales performance though its products.